Istnienie bądź nieistnienie osoby prawnej jako metafizyczny problem nauk prawnych - Kanon, Marcin (PRAWO i WIĘŹ, 2025)
The subject of legal personality is interesting not only from the perspective of legal practice. The concepts developed in the theoretical-legal literature on the nature of legal persons contain numerous elements from epistemology and metaphysics. This makes it possible to examine the influences of philosophy on the legal sciences and to classify certain theories according to non-legal criteria. This paper analyses the fictitious theory of legal personality in terms of its possible hypostasis. The discussion is conducted from the perspective of the position of moderate philosophical realism.